Deposition-environment-dependent structural and magnetic property modification of [111]-oriented epitaxial CoFe2O4 films. Issue 11 (1st August 2020) - Lee, Dooyong; Ju, Tae-Seong; Cho, Chang-Woo; Lee, Jisung; Kim, Hyegyoung; Won, Jong-Han; Choi, Kyoung Soon; Park, Se-Jeong; Lee, Jouhahn; Park, Sungkyun
Abstract: We examined the magnetic, structural, and chemical properties of CoFe2 O4 films deposited on Al2 O3 substrates using RF-magnetron sputtering under Ar and Ar + O2 environments. Perpendicular magnetic anisotropy with large magnetization was observed in the case of the film deposited under the Ar + O2 environment. However, no significant anisotropy appeared in the film deposited under the Ar environment. Interestingly, depth-dependent X-ray photoelectron spectra showed nearly identical stoichiometric ratios of Co/Fe and oxygen vacancies regardless of the deposition environment. Structurally, high-quality crystallinity with in-plane compressive strain, and lower surface and interfacial roughness were induced in the film deposited under the Ar + O2 environment. Cross-sectional transmission electron microscopy and X-ray reflectivity measurements showed that oxygen not only suppressed the deposition rate but also increased the electron density of the film, resulting in better crystallinity. Hence, the presence of oxygen during deposition should be considered as one of the essential parameters for improving the structural and magnetic properties of ferrite films.